The level of integration of moral values in secondary education: Instrument validation - Florina-Gratiela Schiopu-Constantin (Journal of Educational Studies)
At the beginning of this millennium scholars pay more and more attention to the idea of transmitting and implementing values in nowadays’ society. In this context, the transmission and implementation of values is seen as taking place both in the family and at school, thus fully accepting the importance of these two institutions. This also focuses on the idea that the most important endeavor of educators should not be on sharing knowledge to their students, but rather to develop reliable individuals who can successfully face our society’s complexities. The present research deals with the values of responsibility, integrity and self-control and proposed an instrument which measures these values. The proposed instrument was tested in Mihai Ionescu Highschool, Bucharest, Romania, on a sample of 102 students, and then in Theological Adventist Highschool, Craiova, 131 students, aged 11-18. There were 110 boys and 123 girls. The research design is Quantitative. Item analysis, exploratory factorial analysis, and reliability analysis led to item selection and also the final design. The instrument was given the name of RIS- Scale. For the initial instrument there were 32 items. After studying the instrument through factor analysis, the four dimensions of the instrument have been identified. Initially, the components were responsibility, integrity, self-control, and perseverance. Once the factor analysis was completed, it was discovered that the 4th component included a different item structure than the initial one, so it was decided to redefine it having fewer items than it was initially meant. The determination of validation and reliability was carried out in pilot sampling. The reliability coefficient of the 14 items of the scale is good, with a Cronbach's Alpha of 0.89 and an explained variance of 60%. Future research will help in the subsequent enrichment of the instrument.